2010
DOI: 10.1007/s10682-010-9409-y
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic selection on floral scent: trade-off between attraction and deterrence?

Abstract: Flowers emit a large variety of floral signals that play a fundamental role in the communication of plants with their mutualists and antagonists. We investigated phenotypic selection on floral scent and floral display using the rewarding orchid species Gymnadenia odoratissima. We found positive directional selection on inflorescence size, as well as positive and negative selection on floral scent compounds. Structural equation modeling showed that ''active'' compounds, i.e. those that were shown in earlier inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 54 publications
3
86
1
2
Order By: Relevance
“…Moreover, as scent sampling methods, chemical analyses and data handling of the large data sets produced by measuring scent bouquets advance, [27][28][29] large-scale field-based ecological experiments are becoming more attainable. 6,[30][31][32] Thus, future floral evolutionary research will likely increasingly incorporate scents to understand how integrated floral phenotypes evolve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as scent sampling methods, chemical analyses and data handling of the large data sets produced by measuring scent bouquets advance, [27][28][29] large-scale field-based ecological experiments are becoming more attainable. 6,[30][31][32] Thus, future floral evolutionary research will likely increasingly incorporate scents to understand how integrated floral phenotypes evolve.…”
Section: Discussionmentioning
confidence: 99%
“…5 Of course, scent blends are generally composed of many volatiles and, thus, it is possible that different components of the blend will be under different forms of selection. 6 However, due to the difficulty of conducting large-scale scent collections in the field, as well as the necessity of specialized equipment and expertise, our knowledge of the evolutionary ecology of scents is elementary. Therefore, incorporating floral chemistry into studies that include floral color, size and density of display should provide unbiased measurements of the relative importance of scent, particularly in systems in which it is not a conspicuous trait.…”
Section: Phenotypic Selection On Floral Scentmentioning
confidence: 99%
“…The production of such a diverse array of compounds is likely to incur energetic (Gershenzon 1994;Wright and Schiestl 2009) and ecological costs, because the same compounds that attract mutualistic insects also may attract antagonistic herbivores and seed predators (Irwin et al 2004;Proffit et al 2007;Schiestl et al 2011;Theis 2006;Theis and Adler 2012;Wright and Schiestl 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the possibility to measure phenotypic selection on floral scents (e.g., Schiestl et al 2011). However, a challenge is to rigorously define the trait or phenotype.…”
Section: # Springer Science+business Media New York 2014mentioning
confidence: 99%
“…Thus, exploring scent data through statistical techniques and ecologically relevant handling of scent blends (e.g., antennally active vs. non-active scents, (Schiestl et al 2011)) will enhance our ability to detect selection on this complex trait.…”
Section: # Springer Science+business Media New York 2014mentioning
confidence: 99%